2019
DOI: 10.1038/s41467-019-11633-8
|View full text |Cite
|
Sign up to set email alerts
|

Cortical reliability amid noise and chaos

Abstract: Typical responses of cortical neurons to identical sensory stimuli appear highly variable. It has thus been proposed that the cortex primarily uses a rate code. However, other studies have argued for spike-time coding under certain conditions. The potential role of spike-time coding is directly limited by the internally generated variability of cortical circuits, which remains largely unexplored. Here, we quantify this internally generated variability using a biophysical model of rat neocortical microcircuitry… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 66 publications
5
52
0
Order By: Relevance
“…We have further demonstrated that this leads to changes in the activity patterns of the circuit, specifically a reduced reliability of the population response to thalamic input. It has been shown that reliable responses are linked to increased correlations of synaptic inputs (Nolte et al, 2019; Wang, Spencer, Fellous, & Sejnowski, 2010), and we previously observed that such input correlations can be generated by directed simplex motifs with stronger correlations found in larger simplices (Reimann, Nolte, et al, 2017).…”
Section: Resultsmentioning
confidence: 68%
See 4 more Smart Citations
“…We have further demonstrated that this leads to changes in the activity patterns of the circuit, specifically a reduced reliability of the population response to thalamic input. It has been shown that reliable responses are linked to increased correlations of synaptic inputs (Nolte et al, 2019; Wang, Spencer, Fellous, & Sejnowski, 2010), and we previously observed that such input correlations can be generated by directed simplex motifs with stronger correlations found in larger simplices (Reimann, Nolte, et al, 2017).…”
Section: Resultsmentioning
confidence: 68%
“…Spontaneous activity in the NMC-model is variable and chaotic, yet, thalamic stimuli can evoke highly reliable responses (Nolte, Reimann, King, Markram, & Muller, 2019). To study the impact of higher-order structure on this evoked activity, we next stimulated the NMC- and cloud-models with thalamic input (Figure 6A1, see Methods).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations